Online Support Group For Chronic Disease Patients in The Context of Health Communication on Social Media - Azizun Kurnia Illahi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In the context of health communication, support groups are believed to act as a protective measure against detrimental physical and psychological effects for patients by promoting adaptation both endocrinologically (related to hormones), cognitively, and behaviorally. Such adaptation also brings benefits in enhancing the immune system, adherence to medication consumption, and improving patient health. Support groups are crucial for patients, especially those with similar conditions, as there is a higher level of empathy, mutual information sharing, messages of hope and inspiration, and a platform for expression to enhance the life expectancy of patients with chronic diseases. These support groups emerged since the 1970s, constituting an integral component of healthcare. The existence of support groups is closely linked to helping improve health outcomes and reduce patient mortality rates. The diagnosis given by doctors to individuals can be a traumatic event. In such conditions, effective support systems are needed. These support systems can include friends, family, doctors, or other patients who have experienced similar illnesses. The similarity among members of the support group makes them a